Scientific peer review : guidelines for informative peer review - Starck, J. Matthias (Springer Spektrum, 2017)
J. Matthias Starck comprehensively guides the reader in this essential through all steps of writing an expert review for a scientific journal. It is built on a succinct analysis how science works, how science is communicated and how science is published. It provides a critical guide how to write good, informative and fair peer reviews. The author presents a critical discussion of different peer review procedures and their alternatives, explains ethical guidelines as well as the dark sides of scientific publishing. So this essential helps the reader to perform better in the existing system and to contribute to its further development and improvement. Contents Essence of Scientific Communication Why Peer Review? Responsibilities of the Reviewer and Ethical Rules in the Reviewing Process Critique and Variations of the Journal Peer Reviewing Process Reviewer Recognition Institutions and Committees/Recommendations in Conflict Target Groups Advanced PhD students and postdocs from biomedical research and natural science fields who received their first peer review requests and now seek advice and guidance Researchers from all fields of science and all degrees of experience who wish to improve and develop their methodological approach to peer review The Author Prof. Dr. J. Matthias Starck is Professor of Zoology, Department Biology II, at the Ludwig Maximilian University of Munich.
Keywords: Academic writing.; Technical writing.; Peer review.; Scholarly publishing.; elektronické knihy; electronic books